Who is the Prefect? A Comparative Analysis of the Professionalization and Politicization of the Prefect in Romania and Poland in 2021 - Constantin Marius Profiroiu; Ionuț Ciprian Negoiță (Transylvanian Review of Administrative Sciences, 2022)
This present research brings into focus the figure of the prefect and wojewód seen at the crossroads between career public servants representing the interests of the Government and political agents, appointed and dismissed at the whim of the Prime Minister. This paper approaches the issue of the holder of the prefect’s office in Romania and Poland employing a prosopographic analysis and applies a Multiple Linear Regression (MLR) on select items in order to identify the general trend and particularities of their profiles. This institution was structured and articulated at the confluence of some administrative and political actions and integrated in the national institutional framework as a key actor, which continues to connect the institutional capacity of the state and the political capacity of the Government. Moving beyond the legal framework and institutional design of each country, we look at the profile – involving educational, professional and political affiliation – of the people actually appointed to this position in order to ascertain the weight of each of these factors when called to serve in office.